A Conceptual Review and Methodological Design on College Students Attitude Towards Aging Workforce: A Case Study of Southern Thailand - Adulyarat, Medina; Adulyarat, Najmee (Science, Technology, and Social Sciences Procedia, 2023)
In an increasing number of countries, including Thailand, the aging population is a growing concern. As the population ages, understanding attitudes toward aging workers becomes increasingly important, including among college students who will eventually work with and become older workers. Thus, it is crucial to understand college students’ attitudes toward aging workers and their willingness to continue working as the population ages. In Southern Thailand, college students’ attitudes are especially important for the region’s socioeconomic future. This paper presents the conceptual and methodological framework of the study, which aims to explore the attitudes of college students in Southern Thailand toward aging workers and to identify the socio-demographic factors that influence these attitudes and their willingness to continue working in later life. Using an online quantitative survey, data will be collected from approximately 400 college students enrolled at 3 universities namely, Walailak University in Nakhon Si Thammarat province, Prince of Songkla University (Hatyai campus) in Songkla Province, and Princess of Naradhiwas University in Narathiwat province, Southern Thailand. The result will shed light on how college students view older workers and their propensity to work beyond the current retirement age as well as providing policymakers, employers, and other stakeholders with recommendations to enhance attitudes toward older workers among college students in Southern Thailand.